Exploration of Groundwater Potential Zones: A Case Study In Phuentsholing - Thapa, Monika; Yuden, Kezang; Acharya, Saroj (Bhutan Journal of Research and Development, 2022)
In places where surface water sources are insufficient for drinking purpose, groundwater serves as an alternative source. This report highlights all the different methods that can be used for exploration of the groundwater and to analyse this different exploration methods considering various parameters such as economy, suitability, accuracy, etc, hence providing an individual with various choices regarding the selection of particular method during the exploration of groundwater potential zone. Considering the availability of the instrument in Department of Geology and Mines (DGM) and the economic factor in our project, seismic refraction Tomography (SRT) and Geographical Information System (GIS) was used to delineate the potential zones of groundwater in Phuentsholing, Bhutan. GIS focuses on the surface features for groundwater indicator while SRT identify the subsurface layers and the depth of groundwater. The various information regarding existing bore well in the study area were also collected to validate the potential zones developed both by surface and subsurface method.